Green Infrastructure Finance : Leading Initiatives and Research - Baietti, Aldo (Washington, DC: World Bank, 2013)
Investments in green projects are constrained by multiple factors: 1) numerous financial and institutional constraints; 2) pronounced risks; 3) unfavorable structure of cash flow profiles; 4) anti-green market distortions. In order to boost investment flows private financing is essential, but the public and private sectors need to work together. Public instruments and concessional funding will, therefore, need to be used carefully to leverage private flows. This stocktaking report is an initial step in the work on green infrastructure finance. Its objective is to document and summarize current initiatives and leading approaches related to the challenges described as well as present the possible solutions that have been proposed. 'Green infrastructure finance', as defined in this report, is a combination of financial and nonfinancial interventions and instruments that can be utilized for making green investments in infrastructure more affordable and less risky to private sponsors, financial markets and governments. The definition is applied broadly and beyond solely financial instruments with the assumption that more suitable policies and programs are equally needed to increase the attractiveness of green investments. This work is a presentation and is not intended to be an analytical assessment of the body of research. However, this summary, besides highlighting the main conclusions of the research, also provides an assessment of the gaps in the current body of work.